Strategi Marketing Communication Dalam Memasarkan Produk Telkomsel Melalui Akun Instagram @telkomselsumatera - Husna, Filzati; Adhani, Abrar (Universitas Muhammadiyah Sumatera Utara, 2024)
PT. Cellular Telecommunications is a state-owned institution operating in the telecommunications sector. For this reason PT. Cellular Telecommunications continues to create programs to attract public interest in its products. To achieve success in marketing its products, of course PT. Cellular Telecommunications has prepared several marketing communication strategies before marketing its products in order to increase interest in these products. Therefore, this research aims to determine the marketing communications of PT. Cellular Telecommunications in increasing public interest in its products through advertising on Instagram social media. The method used in this research is a qualitative research method with a descriptive approach with data collection through interviews and documentation. These results indicate that PT. Cellular Telecommunications has a strategy for marketing its products through Instagram social media.